THE IMPACT OF GREEN MARKETING AND CORPORATE SOCIAL RESPONSIBILITY ON BRAND IMAGE, PURCHASE INTENTION, AND PURCHASE DECISION (STUDY ON THE BODY SHOP IN SAMARINDA) - Mursandi, Doddy Adhi; Sudirman, Hudyah Astuti; Militina, Theresia (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to analyze and determine the influence of green marketing and corporate social responsibility on brand image, purchase intention, and purchase decision on The Body Shop's customers in Samarinda. This study uses a quantitative approach using SmartPLS software. The sample was 152 respondents with a sampling technique using accidental sampling. The results showed that green marketing is a significantly positive effect on brand image. Green marketing is a significantly positive effect on purchase intention. Corporate social responsibility is not a significantly positive effect on brand image. Corporate social responsibility is a significantly positive effect on purchase intention. Green marketing is a significantly positive effect on the purchase decision. Corporate social responsibility is not a significantly positive effect on the purchase decision. Brand image is a significantly positive effect on the purchase decision. Purchase intention is a significantly positive effect on the purchase decision.